Farmer willingness to pay for seed-related information: rice varieties in Nigeria and Benin - Horna, Daniela; Smale, Melinda; von Oppen, Matthias (International Food Policy Research Institute, 2005)
This study examines farmers’ preferences for seed of new rice varieties and their willingness to pay for seed-related information in villages of Nigeria and Benin. Conjoint analysis is used to estimate the structure of farmers’ preferences for rice seed given a set of alternatives. Farmers are considered to be consumers of seed as a production input, preferring one variety over another based on the utility they obtain from its attributes, which depends on their own social and economic characteristics, including whether or not they sell rice.